2013
DOI: 10.1152/jn.00353.2012
|View full text |Cite
|
Sign up to set email alerts
|

State dependence of adaptation of force output following movement observation

Abstract: Wanda PA, Li G, Thoroughman KA. State dependence of adaptation of force output following movement observation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
8
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 47 publications
(57 reference statements)
2
8
1
Order By: Relevance
“…In previous studies involving the same paradigm used here it has been shown that changes in movement curvature following observation are modulated in opposite directions based on the direction of the observed force field [3,5,21]. In another recent study it was shown that following observation, movements in force-channel trials exhibited systematic changes in the magnitude and direction of the force applied by subjects—changes that mirrored the direction of the observed force field [9]. …”
Section: Resultsmentioning
confidence: 74%
See 2 more Smart Citations
“…In previous studies involving the same paradigm used here it has been shown that changes in movement curvature following observation are modulated in opposite directions based on the direction of the observed force field [3,5,21]. In another recent study it was shown that following observation, movements in force-channel trials exhibited systematic changes in the magnitude and direction of the force applied by subjects—changes that mirrored the direction of the observed force field [9]. …”
Section: Resultsmentioning
confidence: 74%
“…For instance, individuals can learn how to reach in novel dynamical environments (‘force fields’) by observing the movements of a tutor. Action observation promotes sensory-motor plasticity and behavioral changes in both the motor and sensory domains [39]. However, it remains unclear how the brain maps visual information about the movements of others onto motor circuits for learning.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A series of studies has demonstrated that action observation can facilitate force field (FF) adaptation (Bernardi et al 2013;Brown et al 2009;Mattar and Gribble 2005;Wanda et al 2013). FF adaptation is one form of motor learning in which well-learned movements are adapted to externally applied forces.…”
Section: Introductionmentioning
confidence: 99%
“…Observational motor adaptation describes how individuals can learn to respond to novel sensorimotor perturbations by observing someone else adapt their movements to those same perturbations. Observation has been shown to facilitate visuomotor adaptation [46][47][48], force-field adaptation [46,57,58], and force estimation [59,60]. For example, in experiments probing the effects of observation on subsequent visuomotor adaptation [61][62][63], participants observe someone else learning to reach using rotated visual feedback.…”
Section: Open Accessmentioning
confidence: 99%